Physicochemical and Organoleptic Characteristics of Velva Guava Crystal with the Addition of Combrang Juice and CMC - Nurinindya indhayu; Sarofah Ulya; Jariyah Jariyah (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
This research aims to ascertain the impact of CMC and kecombrang fruit juice addition on crystal guava Velva's organoleptic and physicochemical properties and the optimal treatment regimen to yield velva with the best properties. The two-factor factorial pattern utilized in this study's fully randomized design (CRD) has three repetitions. Factor I include 5%, 10%, and 15% of kecombrang fruit juice (v/v). Factor II, namely the addition of 0.5%, 0.75%, and 1% CMC. The conclusion in this study was 15% kecombrang fruit juice and 1% CMC concentration, which produced crystal guava velva with an antioxidant activity value of 41.543%; crude fiber content 6.270%; melting time 17.37 minutes/20gr; viscosity 4203 mPas; overrun 22.03 %; total solids 39.06 %; and the hedonic organoleptic test includes color 3.63; aroma 3.10; texture 3.73 and taste 3.27. The conclusion of this study shows that velva guava crystal has met the quality standards of velva.